Development of a size-separation technique to isolate Caenorhabditis elegans embryos using mesh filters - Nikita S. Jhaveri; Maya K. Mastronardo; J.B. Collins; Erik C. Andersen (PLoS ONE, 2025)
The free-living nematode Caenorhabditis elegans has been routinely used to study gene functions, genetic interactions, and conserved signaling pathways. Most experiments require that the animals are synchronized to be at the same specific developmental stage. Bleach synchronization is traditionally used to obtain a population of staged embryos, but the method can have harmful effects on the embryos. The physical separation of differently sized animals is preferred but often difficult to perform because some developmental stages are the same sizes as others. Microfluidic device filters have been used as alternatives, but they are expensive and require customization to scale up the preparation of staged animals. Here, we present a protocol for the synchronization of embryos using mesh filters. Using filtration, we obtained a higher yield of embryos per plate than using the standard bleach synchronization protocol and at a scale beyond microfluidic devices. Importantly, filtration has no deleterious effects on downstream larval development assays. In conclusion, we have exploited the differences in the sizes of C. elegans developmental stages to isolate embryo cultures suitable for use in high-throughput assays.